Postoperative Outcomes in Ustekinumab-Treated Patients Undergoing Abdominal Operations for Crohn's Disease. (6th December 2017) - Lightner, Amy L; McKenna, Nicholas P; Tse, Chung Sang; Hyman, Neil; Smith, Radhika; Ovsepyan, Gayane; Fleshner, Phillip; Crowell, Kristen; Koltun, Walter; Ferrante, Marc; D'Hoore, Andre; Lauwers, Nathalie; et al.
Abstract: Background: Ustekinumab, a monoclonal antibody targeting interleukins-12 and -23 is used to treat adults with Crohn's disease [CD]. We determined the 30-day postoperative infectious complication rate among CD patients who received ustekinumab within the 12 weeks prior to an abdominal operation as compared with patients who received anti-tumor necrosis factor [TNF] agents. Methods: A retrospective chart review of adults with CD who underwent an abdominal operation between January 1, 2015 and May 1, 2017 was performed across six sites. Surgical site infection [SSI] was defined as superficial skin and soft tissue infection, intra-abdominal abscess, anastomotic leak, and mucocutaneous separation of the stoma. Results: Forty-four patients received ustekinumab and 169 patients received anti-TNF therapy within the 12 weeks prior to surgery. The two groups were similar, except anti-TNF patients were more likely to have received combination therapy with an immunomodulator [ P = 0.006]. There were no significant differences in postoperative SSI [13% in ustekinumab versus 20% in anti TNF-treated patients, p = 0.61] or hospital readmission rates [18% versus 10%, respectively, p = 0.14], but ustekinumab-treated patients had a higher rate of return to the operating room [16% versus 5%; P = 0.01]. There were no significant predictors identified on multivariable analysis. Conclusions: Of the 44 patients with CD who received ustekinumab within the 12 weeks prior to a major abdominal operation, 13% experienced a 30-day postoperative SSI, not statistically different from the 20% found in the anti-TNF cohort. Ustekinumab treatment within 12 weeks of surgery does not appear to increase the risk of postoperative SSI above that of CD patients treated with anti-TNF medications.